BLUEWASHING: ASSESSMENT OF THE STATE OF ART (Gestão & Regionalidade, 2025)
This research aims to evaluate the academic production concerning the term "bluewashing". To achieve the goal proposed, bibliometric research was realized, associated with a critical analysis, targeting the academic publications on the bluewashing term in the acknowledged scientific databases worldwide (Proquest, Web of Science, Capes, Scopus, Scielo and Spell). That allowed a general mapping of what has been produced on the subject, both quality and quantity, not only to consolidate what has been studied so far, but also to enable a critical analysis to advance the subject in the academy and practice. Therefore, it has been possible to realize that the bluewashing subject, despite responding for a relevant production, is still not very studied by the academy, especially in depth, or even in an integrated and consensus way. Considering this, several discussions were made, and new studies are encouraged.